2007
DOI: 10.1158/0008-5472.can-06-4344
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heat Shock Protein 27–Mediated Resistance to DNA Damaging Agents by a Novel PKCδ-V5 Heptapeptide

Abstract: Heat shock protein 27 (HSP27), which is highly expressed in human lung and breast cancer tissues, induced resistance to cell death against various stimuli. Treatment of NCI-H1299 cells, which express a high level of HSP27, with small interference RNA specifically targeting HSP27 resulted in inhibition of their resistance to radiation or cisplatin, suggesting that HSP27 contributed to cellular resistance in these lung cancer cells. Furthermore, because HSP27 interacts directly with the COOH terminus of the prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Expression of Hsp27 is upregulated in numerous types of tumors (particularly breast, colon, ovarian and head and neck tumors) and promotes unfavorable outcome (Ciocca and Calderwood, 2005). Overexpression of this protein is frequently associated with increased resistance to radiotherapy and to anti-cancer drugs, such as cisplatin, doxorubicin and etoposide (Hansen et al, 1999;Kim et al, 2007;Zhang and Shen, 2007). Others and we have shown that targeting Hsp27 by antisense strategy increases cancer cell death in vitro and in vivo (Aloy et al, 2008;Matsui et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Expression of Hsp27 is upregulated in numerous types of tumors (particularly breast, colon, ovarian and head and neck tumors) and promotes unfavorable outcome (Ciocca and Calderwood, 2005). Overexpression of this protein is frequently associated with increased resistance to radiotherapy and to anti-cancer drugs, such as cisplatin, doxorubicin and etoposide (Hansen et al, 1999;Kim et al, 2007;Zhang and Shen, 2007). Others and we have shown that targeting Hsp27 by antisense strategy increases cancer cell death in vitro and in vivo (Aloy et al, 2008;Matsui et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…Hsp27 has been reported to induce high resistance to some of the drugs used in chemotherapy (Hansen et al, 1999;Kim et al, 2007;Zhang and Shen, 2007). To assess effects of PAs on drug response, HeLa cells transfected with PA11 or PA50 were treated for 18 h with cisplatin or doxorubicin.…”
Section: Inhibition Of Hsp27 Anti-apoptotic Activity By Pas In Hela Cmentioning
confidence: 99%
“…HSPB1 plays crucial roles in carcinogenesis and progression through inhibition of cell apoptosis and senescence, two essential traits of cancer cells (48 -50). Various human cancers have been reported to exhibit overexpression of HSPB1, and the tumorigenic potentials of HSPB1 have been demonstrated in both experimental animal models and cell biologic studies (51)(52)(53). HSPB1 has been considered as an independent prognosis marker for cancers because its overexpression was involved in chemoradiotherapeutic resistance of tumor cells (54).…”
Section: Knockdown Of Gstp1 Increased the Susceptibility Of Human Bromentioning
confidence: 99%
“…4 It may be necessary to determine the domain of CAGE that interacts with PKC␣ or PKC␦. Heptapeptide derived from the binding domain of PKC␦ to HSP27 was able to restore sensitivity to radiation and cisplatin in NCI-H1299 lung cancer cells (50). This approach could be employed for the development of CAGE-derived peptides to enhance sensitivity to drugs.…”
Section: Discussionmentioning
confidence: 96%